Do Vulnerable Citizens (Really) Perceive Higher Bureaucracy Costs? Testing a Key Claim of the Administrative Burden Framework - Rick Vogel; Anne Dahlweg; Fabian Hattke (Public Administration Review, 2025)
A key claim of the administrative burden framework is that vulnerable citizens are more affected by administrative burden than others. We test this assumption using the life events survey in Germany, an official data record covering more than 10,000 administrative encounters involving more than 5000 citizens. We find support only for the psychological costs of perceived discrimination, whereas neither compliance nor learning costs are positively associated with vulnerability. On the contrary, some vulnerable groups perceive significantly lower learning and compliance costs. Post hoc analyses suggest that these groups might feel less exposed to bureaucracy because they use fewer sources of information. Further, the results also indicate that citizens' tolerance toward burden decreases with every additional administrative encounter and that previous research has missed an important distinction between absolute and relative burden.
Keywords: 340; administrative burden; administrative costs; discrimination; intersectionality; red tape; state-citizen interactions